The place of phonetics in teaching and learning an FFL : a case study of French in Nigerian secondary schools (2011)
It has been observed that most of the Nigerian French teachers qualified to teach in (he Junior Secondary Schools are not linguistically competent enough. Those with a Francophone background who speak fluently are alleged to lack teaching skills. Within the framework of a communicative method which gives credence lo more oral communication at the beginners’ stage, it is expected that French teachers at the JSS level will do a lot of oral practice with their pupils. As oral practice requires good pronunciation, ascertaining the phonetic competence of the teachers and improving on it will be important. The workshops organized by the Centre for French Teaching and Documentation of Oyo State for French Teachers of JSS level in Oyo and Kogi States are under scrutiny. Questionnaires, tests and a reading passage were used to evaluate the selected teachers’ theoretical and practical knowledge and the methodology of phonetic correction in class. Results show the teachers’ weaknesses in all areas of phonetic knowledge and practice in the classroom. This article presents the facts concerning the teachers’ level in phonetics and reading and proffers some ways forward in the usage of phonetics in class and the requirements to incorporate it in the general curriculum of French as a foreign language in Nigeria at the beginners’ level